OPTIMASI SHIELDING NEUTRON PADA THERMALIZING COLUMN REAKTOR KARTINI - Nurlaili, Fidayati; Azam, M.; Firduasi, K. Sofjan; Widarto, Widarto (BERKALA FISIKA, 2008)
Shield optimization and the calculation of neutron flux the coming out of the thermalizing column of the Kartini reactor have been conducted.The neutron flux will decrease exponentially as it passes the thermalizing column. The thermalizing column of Kartini reactor consists of many different kinds of shields, i.e, graphite, lead, paraffin and an empty chamber of air, therefore the neutron flux count that is coming out of the thermalizing column can be calculated and the shields within the column can be optimized to give smallerÂ neutron flux.Calculation result indicates that the neutron flux coming out of the thermalizing column is 2,681Ã—10-11 cacah cm-2s-1. After optimization, the remaining flux coming out of the thermalizing column is 1,042Ã—10-28cacah cm-2s-1. Key words: thermalizing column, Shield, neutron flux